A 210Pb–226Ra–230Th–238U study of Klyuchevskoy and Bezymianny volcanoes, Kamchatka - Turner Simon; Sims Kenneth W.W.; Reagan Mark; Cook Craig (Geochimica et Cosmochimica Acta, 2007)
Lavas from Klyuchevskoy and Bezymianny volcanoes, Kamchatka, appear to show a link between the extent of partial melting in their mantle source region and the subsequent degree of fractionation suffered by the magmas during passage through the crust. This fractionation may have occurred on timescales significantly less than 1000 years if observed 226Ra excesses largely reflect variable residual porosity in the source melting region. Unlike most arc lavas, those with the highest MgO contents and Ba/Th ratios have the lowest 226Ra excess. Forward models suggest that those portions of the source which had undergone the greatest addition of U by fluids from the subducting plate also underwent the greatest extents of partial melting at the highest residual porosity. At Kluchevskoy, a change from eruption of high-MgO to high-Al2O3 basaltic andesites around 1945 is reflected in an increase in size of 226Ra excess which seems to require a simultaneous decrease in residual porosity and suggests a rapid changes in the melting regime. The eruption of andesites at Bezyminanny, simultaneous with the eruption of basaltic andesites at Klyuchevskoy, further suggests that different degree melts produced at differing residual porosity can be formed and extracted from the melt region at the same time. Thus, the melting processes beneath Klyuchevskoy and Bezyminanny are demonstrably complex. They have clearly been influenced by both fluid addition from the subducting plate and extension and decompression beneath the Central Kamchatka Depression. Finally, the 210Pb data are, with one or two exceptions, in equilibrium with 226Ra, suggesting that there was restricted relative magma-gas movement in this highly productive magmatic system.